Effectiveness of different tests in the diagnosis of Ocular Myasthenia gravis - Luna, Mahfuja Khanam; Bhuiyan, Mohammad Monzurul Alam; Uzzaman, Md Akter; Zeba, Israt Jahan; Peea, Amina Jannat; Akhter, Mst Shammy; Rahman, Tasnim (Journal of Dhaka National Medical College & Hospital, 2024)
Background: Myasthenia gravis (MG) is an autoimmune neuromuscular disease leading to fluctuating muscle weakness and fatigue. Diagnostic tests include serum acetylcholine receptor antibody levels, Single fiber electromyography (SFEMG), Repetitive Nerve Stimulation (RNS) test, Neostigmin test, the sleep test, the rest test and the Ice pack test. Objectives: To evaluate the importance and effectiveness of Ice pack test, Neostigmin test and RNS (Repetitive nerve stimulation test) in diagnosis of Myasthenia Gravis. Materials and Methods: A hospital basedprospective observational study was done in the Neuro-ophthalmology department in National Institute of Ophthalmology & Hospital, Dhaka(January 2014 to December 2014) among 30 patients who came with complaints of variable amount of ptosis and diplopia attending the neuro-ophthalmology department of NIO & H and who provided written informed consent were enrolled in the study. Those who came with any other ocular pathology or history of previous ocular surgery were not included in this study. The variable includes in this study were Gender, Age, Amount of ptosis, LPS function, Margin reflex distance, Ocular motility tests. We have performed the Ice pack test, then with proper arrangements Neostigmine test have been done in operation theater having emergency resuscitation and finally we refer all those patients to NINS & H (National Institute of Neuroscience & Hospital) for doing RNS (Repetitive nerve stimulation test), as our hospital does not have the facility for doing RNS test. Results: Mean age was 31.72+6.46 years. Male preponderance was seen (56.67% of the cases). Most of the patients among them were within the age group of 11-20 years of age (40%). Ice pack tests was positive for 28 patients (93.33%) among 30 patients. Neostigmin test was also positive for 27 patients (90%) among of 30 patients. RNS test was positive only for 9 patients (32.1% ). RNS test could not performed by 2 patients who were 5 & 6 years old respectively. Conclusion: Most cases of clinically diagnosed Myasthenia gravis was positive by Ice pack tests (sensitivity 93.33%) and Neostigmin test (Sensitivity 90%). But RNS test was positive only those have systemic involvement or general Myasthenia Gravis (sensitivity 31.2%). So, it is not so effective test for diagnosis of ocular myasthenia gravis. J. Dhaka National Med. Coll. Hos. 2024; 30 (01): 07-12